The Integration of 5G Technology in Smart Cities: Challenges and Solutions - Almahdi Mosbah Almahdi Ejreaw (African Journal of Advanced Pure and Applied Sciences, 2023)
Smart cities require advanced communication to share information and connect people from the cities and outside the cities. Today wireless technology is important to support mobility in communication. With advanced wireless communication adapted to smart cities, users can move and at the same time communicate with people in any corner around the cities. Speed and connectivity in communication represent the two important factors in smart cities communication systems. To have a high speed and stable connection in wireless communication technology, the 5G technology in communication systems is introduced. 5G technology not only can offer high speed and better connection in wireless communication but also offers more bandwidth to support large users. Besides that, 5G also supports the Internet of Things. This research paper presents a systematic review on the integration of 5G technology used in smart cities. The research will show the published papers on 5G technology used in smart cities from the year 2020 to 2023. Two databases will be used as references to support the reviews. The databases used are Google Scholar and Mendeley. At the end of the research, the challenges, and the solutions to improve the integration of 5G technology into the smart cities will be presented.